Strategi Branding Sekolah MAN 1 Batam Dalam Membangun Citra Creating A Successful Qurani'c Di Era Digital - Azhra Azhra; Riswandi Riswandi (LPPM Universitas Putera Batam, 2026)
This study examines the school branding strategy of Madrasah Aliyah Negeri (MAN) 1 Batam in building the institutional image of Creating a Successful Qur’anic Generation in the digital era. The research is grounded in the growing demand for educational institutions, particularly Islamic schools, to strengthen their identity and competitiveness through digital branding. Employing a qualitative descriptive approach with an instrumental case study design, data were collected through in-depth interviews, observation, and documentation involving key stakeholders, including the headmaster, public relations staff, teachers, student affairs officers, students, and parents. The findings reveal that branding at MAN 1 Batam is not merely promotional but functions as a value-based and collaborative process. The headmaster acts as the initiator of brand identity, public relations serve as the executor of digital communication, teachers and student affairs reinforce internal brand values, students emerge as co-creators of institutional image, and parents function as public legitimators. From the perspective of Integrated Marketing Communication (IMC) and digital branding, MAN 1 Batam demonstrates message consistency across multiple digital platforms; however, challenges remain in terms of human resource limitations, content consistency, and students’ exposure to negative digital influences. This study contributes to the discourse on educational branding by emphasizing the importance of actor synergy, value internalization, and digital engagement in shaping a sustainable and credible school image